An extrapolation method for reducing equilibration times in sedimentation equilibrium experiments. - Correia, J J (1977)
We present a detailed investigation of the use of an extrapolation technique to decrease running times of sedimentation equilibrium experiments. If concentration profiles are available at time delta tau, 2delta tau, 3delta tau,...., cn(r) = c(r, n delta tau), then the Aitken transformation replaces the cn(r) + ĉn(r) = [cn + 1(r) cn - 1(r) - c2n(r)]/[cn + 1(r) + cn - 1(r) - 2cn(r)]. We show that the ĉn(r) converge to the equilibrium values c infinity (r) much more quickly than the cn(r). Savings in time are shown to range from a factor of approximately 2 for meniscus depletion experiments to factors of between 4 and 8 for lower speeds or smaller molecular weights. It is also shown that the technique is quite sensitive to noise, so that an accurate optical system is required to allow its optimal use.